Analysis of Reading Literacy Habituation and Development Stages to Increase Students' Reading Interest in Grade II SDN Pudakpayung 01 Semarang - Almira Jovankova Yunan; Tri Joko Raharjo; Arief Yulianto (Journal of Primary Education, 2022)
Entering the 21st century, students are expected to have the ability to understand information and apply various critical and creative thinking techniques when reading, writing, and solving problems. One of the policies carried out by the Semarang city administration is the implementation of the School Literacy Movement (GLS) and optimizing mobile libraries as a central facility. This study aims to analyze the school's strategy in increasing the Reading Literacy Habituation and Development stage to increase students' reading interest and to analyze the teacher's influence on students in the Reading Literacy Habituation and Development stage to increase students' reading interest in class II at SDN Pudakpayung 01 Semarang. The method used in this research is descriptive qualitative method. Data collection techniques in this study were interviews with class II principals and teachers, grade II students, observation, and documentation. From the results of observing the constraints on the stage of reading literacy comprehension in elementary schools at SDN Pudakpayung 01 Semarang City, that is, most of the students who are still in class II feel lazy to read is still quite high. Meanwhile, even in high grades, there are still many students who are less motivated to read or write. Reading literacy is not just talking 5 about 15 minutes of reading a book. Reading interest literacy is not only influenced by internal factors in school, students' reading interest is also influenced by external factors, namely parents.